Analisis Pengaruhi Indeks Pembangunan Manusia Terhadap Tingkat Kemiskinan Studi Kasus Provinsi Banten - Wibawa, Bintang Putra; Julliansyah, Muhammad Raihan; Desmawan, Deris (Universitas Labuhanbatu, 2022)
Poverty is a concern in every society, especially in new ones. The growing number of poor people brings new issues. Economic development is one method for reducing poverty. The human development index provides indicators of economic growth. In this study, data was analyzed using the SPSS 23 application with a simple linear regression analytical procedure using data from BPS Banten Province in each Regency/City from 2021 to 2012. The data testing results show that the human development index has a significant and negative impact on poverty statistics. As a result, a program or policy that may raise the human development index and hence alleviate poverty is required.